Influence of sowing window, irrigation and fertilizer levels on growth and yield of late sown Indian mustard - Pramod Kumar,; Suresh Kumar,; VS Hooda,; Ram Avtar,; Sheilendra Kumar,; Kapil Malik, (Journal of Oilseed Brassica, 2026)
A study was conducted in the Rabi seasons of 2018-19 and 2019-20 to assess the effect of date of sowing, irrigation andfertility levels on growth and productivity of Indian mustard (Brassica juncea) under late sown condition. Treatmentsimposed were sixteen combinations of two sowing dates viz. 2nd week of November and 4th week of November; twoirrigation levels viz. no post-sown irrigation and one irrigation at flowering stage in main plots and four fertilizer levelsviz. 87.5% RDF, 100% RDF, 112.5% RDF and 125% RDF in sub-plots with three replications. Sowing of mustard crop in2nd week of November recorded significant increase in plant height, dry matter accumulation, number of primary andsecondary branches over the 4th week of November sown crop. On an average, 2nd week of November sowing recordedsignificantly higher seed yield (75.63%) and stover yield (74.50%). Application of one irrigation at flowering stagerecorded a significant increase in plant height, dry matter accumulation, number of primary and secondary branches overthe no post-sown irrigation. Seed and stover yields were recorded significantly higher with one irrigation by 11.95 and14.84%, respectively over the no post-sown irrigation. The increased doses of fertilizers also increased the growth, yieldpamperers, and seed yield as well as stover yield responded significantly up to 125% RDF.